eal-Time Video Frame Differentiator Based on DDR3 SDRAM Memory Interface - Davutoğlu, Doğancan (My University, 2018)
In this paper, design of a real-time video frame differentiator based on an external memory interface is proposed. Furthermore, implementation and simulation processes of the design is discussed. The proposed design is capable of differentiating video frames over time, up to fuIl-HD resolution at 60 Hz frame rate. An external SDRAM memory unit is used within the proposed design and drived by a memory interface. In order to improve the flexibility of the architecture, video resolution, video buffer size on memory and burst size of the memory interface are designed to be user defined and configurable.
Keywords: Real-time Video Processing; Field Programmable Gate Arrays; External Memory Interface; SDRAM; DDR3 Memory